Metal hydride systems for hydrogen storage and supply for stationary and automotive low temperature PEM fuel cell power modules. (21st September 2015) - Lototskyy, Mykhaylo V.; Davids, Moegamat Wafeeq; Tolj, Ivan; Klochko, Yevgeniy V.; Sekhar, Bhogilla Satya; Chidziva, Stanford; Smith, Fahmida; Swanepoel, Dana; Pollet, Bruno G.
Abstract: Metal Hydrides (MH) provide efficient hydrogen storage for various applications, including Low Temperature PEM Fuel Cells (LT PEMFCs), when system weight is not a major and critical issue. Endothermic dehydrogenation of MH leading to decreased rates of H2 evolution eliminates the risk of accidents even in the case of rupture of the hydrogen storage containment. At the same time, it poses a number of challenges related to the constant, stable and sufficient H2 supply for stable FC operation. This paper reviews recent efforts in MH hydrogen storage and supply systems for LT PEMFC applications, including the ones developed at HySA Systems/SAIAMC/University of the Western Cape. The systems are characterised by a series of hydrogen storage capacities ranging from 10 NL to ∼10 Nm 3  H2 in turns providing stable operation for stationary and mobile FC power modules (from a few W to several kW). The MH systems use unstable hydride materials (equilibrium H2 pressure at ambient temperature around 10 bar) that, in combination with special engineering solutions of MH containers (both liquid- and air-heated-cooled), and optimised system layout, facilitates H2 supply to LT PEMFC stacks. Graphical abstract: Highlights: Metal hydrides for H2 storage and its supply to low-temperature PEM FC modules. Storage capacity range from 10 NL to 10 N m 3 H2 ; liquid- and air heated/cooled. Medium stability MH on the basis of AB2 -type alloy used. Heat transfer issues result in incomplete H2 supply to FC at the rated power. Ways of mitigating the specified problem have been successfully implemented.